2008
DOI: 10.1115/1.2909605
|View full text |Cite
|
Sign up to set email alerts
|

Transition in Wall-Bounded Flows

Abstract: In this paper, we present direct comparisons of experimental results on transition in wall-bounded flows obtained by flow visualizations, hot-film measurement, and particle-image velocimetry, along with a brief mention of relevant theoretical progresses, based on a critical review of about 120 selected publications. Despite somewhat different initial disturbance conditions used in experiments, the flow structures were found to be practically the same. The following observed flow structures are considered to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(74 citation statements)
references
References 98 publications
3
70
0
1
Order By: Relevance
“…"Vortex Breakdown" has been widely spread in many research papers and textbooks [5,[9][10][11]. However, our analysis found that "Vortex Breakdown" is theoretically impossible.…”
Section: Vortexmentioning
confidence: 44%
See 1 more Smart Citation
“…"Vortex Breakdown" has been widely spread in many research papers and textbooks [5,[9][10][11]. However, our analysis found that "Vortex Breakdown" is theoretically impossible.…”
Section: Vortexmentioning
confidence: 44%
“…In practice, "Vortex Breakdown" can never happen. It is found that "Vortex Breakdown" described by exiting publications [5,9,10] is either misinterpreted by 2D visualization or by using the pressure center as the vortex center.…”
Section: Vortexmentioning
confidence: 99%
“…2 is exceeded). This process-referred to as bypass transition [22,23]-has been suggested as a critical factor in shear-flow transition to account for discrepancies between experimental findings and analytical forecasts based on normal modes [24]. The second key point is that transient growth can occur on time scales that are comparable to those of the studied process.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was recent studies, such as [68][69][70][71][72][73][74][75], that have revealed much of the detail of such streak formation, in particular their vortical structures. Among them [75] proposed a well-explained streak formation, revealing detailed vortical dynamics as shown in figure 24. The transitional flow structures consist of the T-S wave and Lambda vortex, the soliton-like coherent structures (SCSs), the secondary closed vortex, the chain of ring vortices and the resultant stream-wise vortices.…”
Section: Boundary-layer Streak Breakdown Triggering Cavitation Inceptionmentioning
confidence: 99%
“…Streak structure and breakdown: (a -c) typical hydrogen bubbles in laminar streak formation illuminated by a horizontal laser sheet at different heights [75]; (d) three-dimensional structure reconstructed from these detailed photos [75]. rsfs.royalsocietypublishing.org Interface Focus 5: 20150020 zone as indicated in figure 27; then this breakdown triggers immediately neighbouring streaks, starting breakdowns with tiny time delays, forming the tip of the wedge shape.…”
Section: Boundary-layer Streak Breakdown Triggering Cavitation Inceptionmentioning
confidence: 99%